Payments discourage coordination in ecosystem services provision: Evidence from behavioral experiments in Southeast Asia - Bell, Andrew R.; Zhang, Wei (IOP Publishing, 2016)
The contribution of synthetic pesticides to closing yield gaps around the world is undeniable; however, their use is also a classic double-edged sword. Beyond the well-recognized social costs (e.g., pollution to soil and water, and health effects both on consumers and other species) there are also private costs on farmers beyond the direct costs of inputs, associated with elevated risks of both acute and chronic damage to farmers' health, and with the destruction of populations of beneficial organisms. Managing agricultural land use to enhance natural pest control services (also called mobile agent-based ecosystem services or MABES) holds promise to reduce this growing reliance on pesticides, though it too carries costs. In particular, uncertainty in crop yield due to pest damages, as well as the need to coordinate pesticide use with neighboring farms, can be important obstacles to establishing the longer-term public good of natural pest regulation. Current thinking on promoting ecosystem services suggests that payments or other economic incentives are a good fit for the promotion of public good ecosystem services such as MABES. We undertook a framed field experiment to examine the role of subsidies for non-crop habitat in improving insect-based ecosystem services in two separate samples in Southeast Asia—Cambodia and Vietnam. Our central finding is that these two contexts are not poised equally to benefit from incentives promoting MABES, and in fact may be left worse off by payments schemes. As the study and practice of payments for ecosystem services programs grows, this finding provides an important qualifier on recent theory supporting the use of payments to promote public good ecosystem services—where the nature of the coordination problem is complex and nonlinear, farm systems can be made worse off by being encouraged to attempt it.